ANALISIS FITUR APLIKASI CINCAU STATION DENGAN METODE CUSTOMER KNOWLEDGE MANAGEMET (CKM) - Arya Reinanta Putra, Theofilus Dewa; Maximillian, Louis; Reinaldo, Dionisius; Prutanda, Ryan (Jurnal Nasional Teknologi Komputer, 2023)
In the era of globalization, business competition is fierce, especially in the food and beverage industry. Cincau Station, which initially only served ice cincau with palm sugar, has developed into a variety of flavors and can be accessed through a mobile application. However, this application has shortcomings in design and features that can affect consumer interest. This research uses the Customer Knowledge Management (CKM) method to analyze the UI/UX of the Cincau Station application. CKM is an approach that considers customer needs to develop ideal products. The goal of CKM is to achieve brand effectiveness and competitiveness. This research limits the analysis to the content and composition aspects of the application. Keywords: Cincau Station, Customer Knowledge Management (CKM), Design, Effectiveness, Mobile Application, UI/UX